New biflavonoid and other flavonoids from the leaves of Chimarrhis turbinata and their antioxidant activities - Cardoso, Carmem L. [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Castro-Gamboa, Ian [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (FapUNIFESP (SciELO), 2005)
A new biflavonol, named chimarrhoside (1), and eight known flavonol glycosides (2-9), were isolated from the leaves of Chimarrhis turbinata. Their structures were established on the basis of 1D and 2D NMR experiments as quercetin-3-O-rutinoside (2), kaempferol-3-O-rutinoside (3), kaempferol-3-O-α-L-rhamnopyranosyl-(1→6)-β-D-galactopyranoside (4), quercetin-3-O-α-L-rhamnopyranosyl-(1→6)-β-D- galactopyranoside (5), 6-hydroxy-rutin (6), kaempferol-3-O-D-galactopyranoside (7), kaempferol-3-O-D-glucopyranoside (8) and kaempferol-3-O-α- Lrhamnopyranosyl-(1→6)-α-L-rhamnopyranosyl-(1→4) -β-D-glucopyranoside (9). In addition, catechin (10) and catechin-(4α→8)-catechin-procyanidin B-3) (11) were isolated. The crude extract, fractions and isolated compounds were evaluated for their antioxidative properties using an autographic assay based on β-carotene bleaching on TLC plates, and spectrophotometric detection by reduction of the stable 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical. Flavonoids 2, 5, 6, 10 and 11 displayed strong free radical scavenging activity, when compared with the standards BHT and rutin. ©2005 Sociedade Brasileira de Química.
Keywords: β-carotene; Chimarrhoside; DPPH; Rubiaceae